Chapter Cassiodorus' Variae in the 9th Century - Cristini, Marco (Reti Medievali E-Book, 2022)
The fate of Cassiodorus' Variae during the Early Middle Ages is largely unknown, since the manuscript tradition begins with the eleventh century, and long quotations taken from them are attested only from that period. However, words or expressions reminiscent of the Variae occur more than once in Charlemagne's letters to Byzantium, in the works of Paschasius, and in the Donation of Constantine. The author of the epistles sent by Charlemagne's to the East Roman emperor was aware of the ideological context of Variae 1.1, and the same is true for the Donation of Constantine. At the same time, Paschasius used Cassiodorus as a source of elegant words and expressions, thereby treating him like a classical author. It is impossible to ascertain whether Carolingian writers had access to all books of the Variae, or only to a substantial selection of letters (similar for instance to the manuscript containing the Epistolae Austrasicae), but there is a high degree of likelihood that they knew quite a few epistles of Cassiodorus, and were able to appreciate the political messages conveyed by them.